2019
DOI: 10.1016/j.survophthal.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal versus monofocal intraocular lenses for age-related cataract patients: a system review and meta-analysis based on randomized controlled trials

Abstract: We compare multifocal intraocular lenses (MFIOLs) to monofocal IOLs for visual acuity (VA), contrast sensitivity, and adverse events using data from 21 randomized controlled trials with 2951 subjects. There was no statistical difference between uncorrected distance VA and corrected distance VA. Compared with monofocal IOLs, MFIOLs showed a better performance on uncorrected intermediate VA measured at 60 cm and uncorrected near VA; the mean differences were-0.06 (95% confidence interval [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…5 In their meta-analysis, Cao et al found multifocal lenses provided better near and intermediate vision (both corrected and uncorrected). 8 However, patient-reported outcomes (PROs) have suggested more frequent dysphotopsia and worse contrast sensitivity, especially with low light or glare, with multifocal IOLs than with monofocal lenses. 4,[8][9][10][11][12][13] Glare and halo, caused by the transition zone between the diffractive steps, have been reported to cause patient dissatisfaction with multifocal lenses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In their meta-analysis, Cao et al found multifocal lenses provided better near and intermediate vision (both corrected and uncorrected). 8 However, patient-reported outcomes (PROs) have suggested more frequent dysphotopsia and worse contrast sensitivity, especially with low light or glare, with multifocal IOLs than with monofocal lenses. 4,[8][9][10][11][12][13] Glare and halo, caused by the transition zone between the diffractive steps, have been reported to cause patient dissatisfaction with multifocal lenses.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, patient-reported outcomes (PROs) have suggested more frequent dysphotopsia and worse contrast sensitivity, especially with low light or glare, with multifocal IOLs than with monofocal lenses. 4,[8][9][10][11][12][13] Glare and halo, caused by the transition zone between the diffractive steps, have been reported to cause patient dissatisfaction with multifocal lenses. 9,12 IOLs with a decreased near addition (add) dioptric power have been suggested as a potential remedy for these unsatisfactory PROs.…”
Section: Introductionmentioning
confidence: 99%
“…We have read the article by Cao and coworkers, 1 and believe that some discussion is required. The authors compared the visual acuity, contrast sensitivity (CS) and adverse events in monofocal intraocular lenses and multifocal IOLs (MIOLs).…”
mentioning
confidence: 99%
“…The aim of this review was to assess high-quality evidence based on only randomized controlled trials (RCTs). 1 The risk of bias was assessed in several aspects as recommended by the Cochrane Collaboration;…”
mentioning
confidence: 99%
See 1 more Smart Citation